NaIO4-mediated C-H activation of alkylbenzenes and alkanes with LiBr - Shaikh, T. M.; Sudalai, A. (Tetrahedron Letters, 2005)
NaIO4 oxidizes lithium bromide efficiently under acidic conditions to functionalize alkylbenzenes and alkanes and produce the corresponding bromo and acetoxy derivatives in excellent yields. The protocol also demonstrates the direct conversion of cyclohexane into trans-1,2-dibromocyclohexane in moderate yield. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: alkanes; alkylbenzenes; C-H activation; Lithium bromide; NaIO4

NaIO4-KI-NaN3 as a new reagent system for C-H functionalization in hydrocarbons - Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2008)
The NaIO4-KI-NaN3 combination has been found to be an efficient, reliable, and inexpensive reagent system for mono- and 1,2-difunctionalization of hydrocarbons via C-H bond activation to afford vicinal azido- and acetoxy iodinations of cyclic hydrocarbons. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: azides; C-H activation; Iodination; NaIO4

Ru-catalyzed branched versus linear selective C3-alkylation of 2-aroylbenzofurans with acrylates via C-H activation - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, Chepuri V. (Chemistry-A European Journal, 2014)
The carbonyl-directed C3-H activation and alkylation of 2-aroylbenzo[b]furans with acrylates occurs selectively either in a linear or branched fashion, depending on the catalyst employed; [Ru(p-cymene)Cl-2](2) or Ru(PPh3)(3)Cl-2, respectively. Two alternate pathways-funded upon the differences in steric and electronic preferences of these two complexes-is proposed for the selectivity of linear versus branched products.
Keywords: acrylate; benzo[b]furan; branched-selective alkylation; C-H activation; ruthenium

Electronic control on linear versus branched alkylation of 2-/3-aroylbenzofurans with acrylates: combined DFT and synthetic studies - Srinivas, Kolluru; Dangat, Yuvraj; Kommagalla, Yadagiri; Vanka, Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2017)
Investigations on the factors that govern unusual branched alkylation of 2-aroylbenzofurans with acrylates by Ru-catalyzed carbonyl-directed C-H activation has been carried out by calculating the kinetics associated with the two key steps-the coordination of the acrylate with the intermediate ruthenacycle and the subsequent migratory insertion reaction-studied with the help of DFT calculations. Eight possible orientations for each mode of alkylation have been considered for the calculations. From these calculations, it has been understood that there is a synergistic operation of the steric and electronic effects favoring the branched alkylation. Further DFT investigations on the alkylation of the isomeric 3-aroylbenzofurans indicated a preference for the linear alkylation and this has been verified experimentally. Overall, the observed/calculated complementary selectivity in the alkylation of 2-/3-aroylbenzofurans with acrylates reveals that the substrate-dependent charge distribution of the Ru-C bond in the intermediate ruthenacycle is an important determining factor and thus the current work opens up a new domain of substrate design for controlling regioselectivity.
Keywords: acrylates; Alkylation; aroylbenzofuran; C-H activation; Density functional calculations

Copper- and phosphine-free nickel(II)-catalyzed method for C-H bond alkynylation of benzothiazoles and related azoles - Patel, Ulhas N.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2018)
A phosphine-free nickel(II)-catalyzed method for the C(2)-H bond alkynylation of (benzo)thiazoles, (benz)imidazoles, and oxazoles is described. Well-defined and air-stable (Phen)NiCl2 catalyst efficiently catalyzes the coupling of diverse azoles with alkynyl bromides without the use of a copper co-catalyst, and the method tolerates synthetically important functional groups. Preliminary mechanistic studies on this Ni-II-catalyzed alkynylation emphasize the homogeneous nature of the catalyst, and rule out a radical manifold for the reaction. The synthetic utility of this Ni-catalyzed method is demonstrated by further functionalizing the alkynylated benzothiazoles to 3-methyl-2-(alkynyl)benzo[d]thiazolium salts that are known DNA cleaving agents.
Keywords: alkynylation; azoles; C-H activation; heterocycles; Nickel

Nickel-catalyzed straightforward and regioselective C-H alkenylation of indoles with alkenyl bromides: scope and mechanistic aspect - Jagtap, Rahul A.; Vinod, C. P.; Punji, Benudhar (ACS Catalysis, 2019)
Nickel-catalyzed regioselective C-H bond alkenylation of indoles and related heteroarenes with alkenyl bromides is accomplished under relatively mild conditions. This method allows the straightforward synthesis of C-2 alkenylated indoles employing an air-stable and well-defined nickel catalyst, (bpy)NiBr2, providing a solution to the limitations associated with hydroindolation and oxidative alkenylation. The reaction conceded the coupling of indole derivatives with various alkenyl bromides, such as aromatic and heteroaromatics, alpha- and beta-substituted as well as exo- and endo-cyclic alkenyl compounds. An extensive mechanistic investigation, including controlled study, reactivity experiments, kinetics and labeling studies, and EPR and XPS analyses, highlights that the alkenylation proceeds through a single-electron transfer process comprising an odd-electron oxidative addition of alkenyl bromide. Furthermore, the alkenylation operates via a probable Ni(I)/Ni(III) pathway involving the rate-limiting C-H nickelation of indole.
Keywords: alkenylation; C-H activation; indoles; Mechanism; Nickel; single-electron transfer

Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free

Expeditious and solvent-free nickel-catalyzed c-h arylation of arenes and indoles (vol 10, pg 2242, 2017) - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2020)
Keywords: Arylation; C-H activation; heterocycles; Homogeneous catalysis; Nickel

Iron-catalyzed C(sp(2))-H alkylation of indolines and benzo[h]quinoline with unactivated alkyl chlorides through chelation assistance - Jagtap, Rahul A.; Samal, Pragnya Paramita; Vinod, C. P.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2020)
Regioselective C-H bond alkylation of indolines and benzo[h]quinoline with a wide range of unactivated and highly demanded primary and secondary alkyl chlorides is accomplished using a low-cost iron catalyst. This reaction tolerates diverse functionalities, such as C(sp(2))-Cl, fluoro, alkenyl, silyl, ether, thioether, pyrrolyl, and carbazolyl groups including cyclic and acyclic alkyls as well as alkyl-bearing fatty-alcohol and polycyclic-steroid moieties. The demonstrated iron-catalyzed protocol proceeded via either a five-membered or a six-membered metallacycle. Intriguingly, the C-7-alkylated indolines can be readily functionalized into free-NH indolines/indoles and tryptamine derivatives. A detailed mechanistic investigation highlights the participation of an active Fe(I) catalyst and the involvement of a halogen-atom transfer process via a single-electron-based mechanism. Deuterium labeling and kinetics analysis indicate that the C-H metalation of indoline is the probable turnover-limiting step. Overall, the experimental and theoretical studies supported an Fe(I)/Fe(III) pathway for the alkylation reaction comprising the two-step, one-electron oxidative addition of alkyl chloride.
Keywords: alkyl chlorides; Alkylation; C-H activation; chelation assistance; indolines; iron

Advances in C(sp(2))-H/C(sp(2))-H oxidative coupling of (Hetero)arenes using 3d transition metal catalysts - Bansal, Sadhna; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2021)
C-H/C-H oxidative coupling has emerged as a straightforward and powerful technique for the construction of (hetero)biaryls, with substantial application to drug discovery, agrochemicals, biology, and material sciences. Mainly aryl-aryl, aryl-heteroaryl, and heteroaryl-heteroaryl couplings via double C(sp(2))-H activation using 4d or 5d noble transition metal catalysts have been extensively studied. Considering the earth-abundant and inexpensive nature of 3d transition metals, the sustainable development of C(sp(2))-H/C(sp(2))-H oxidative coupling employing such metal catalysts has gained significant attention. In this review, we present a comprehensive overview of C(sp(2))-H/C(sp(2))-H oxidative coupling of (hetero)arenes catalyzed by 3d transition metals.
Keywords: (hetero)biaryls; 3d transition metal; Biaryls; C-H activation; cross-dehydrogenative coupling

Advances in transition-metal-catalyzed C-H bond oxygenation of amides - Vijaykumar, Muniyappa; Punji, Benudhar (Synthesis-Stuttgart, 2021)
C-O bond formation represents a fundamental chemical transformation in organic synthesis to develop valuably oxygenated (hetero)arenes. Particularly, the direct and regioselective C-H bond oxygenation of privileged amides, using a transition metal catalyst and a mild oxygenating source, is a step-economy and attractive approach. During the last decade, considerable progress has been realized in the direct C-H oxygenation of primary, secondary, and tertiary amides. This Short Review compiles the advances in transition-metal-catalyzed oxygenation of C(sp(2))-H and C(sp(3))-H bonds on various amides with diverse oxygenation sources. The review is categorized into two different major sections: (i) C(sp(2))-H oxygenation and (ii) C(sp(3))-H oxygenation. Each section is discussed based on the directing group (monodentate and bidentate) attached to the amide derivatives.
Keywords: Amides; C-H activation; directing group; Oxygenation; Transition Metal

Dual-catalyst engineered porous organic framework for visible-light triggered, metal-free and aerobic sp(3) C-H activation in highly synergistic and recyclable fashion - Kumar, Gaurav; Dash, Soumya Ranjan; Neogi, Subhadip (Journal of Catalysis, 2021)
Photoredox and organo-catalysis denote powerful construction tools for new classes of carbon-carbon bonds, where incisive amalgamation of both the approaches over a single, recyclable platform can bring about synergic and eco-friendly reactions under mild conditions. Aiming at enamine-based photoredox catalysis for atom-economic and metal-free sp(3 )C-H activation, an amide-based two-dimensional (2D) porous organic framework (POF) is devised. The pendent -NH2 groups are judiciously anchored with two catalytic stations viz. Rose Bengal and L-proline, through stepwise variation of solid phase peptide synthesis. The dual-catalyst engineered POF represents a fully organic material that synergistically performs visible-light triggered oxidative Mannich reaction to produce biorelevant heterocycle beta-amino ketone in excellent yield at room temperature, using oxygen as clean and selective oxidant. Importantly, activity of this bi-functionalized catalyst compares favorably well to individual homogeneous counterparts. The covalently modified framework demonstrates economic viability via gram-scale synthesis besides admirable reusability, and proves to be effective for nineteen varieties of substrates. The photocatalytic path is detailed from efficient energy transfer from host polymer to substrate in light of experimental and theoretical studies, which provides proof-of-concept to the photo-organo combined mechanism. The material benefits heterogenising two homogeneous catalysts, besides excluding additional steps of conventional Mannich reactions, and offers a step-forward to smart and green cross-dehydrogenative coupling reactions. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Atom-economy; C-H activation; Dual-catalyst engineering; Metal-free reaction; Photo-organo catalysis; Porous organic framework

Ni(II)-catalyzed intramolecular C-H/C-H oxidative coupling: an efficient route to functionalized cycloindolones and indenoindolones - Ankade, Shidheshwar B.; Samal, Pragnya Paramita; Soni, Vineeta; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2021)
Nickel(II)-catalyzed intramolecular C(sp(2))-H/C(sp(3))-H and C(sp(2))-H/C(sp(2))-H oxidative couplings in indoles are achieved via chelation assistance. These reactions provide access to biologically relevant five- and six-membered substituted cyclopentaindolones, carbazolones, and indenoindolones in high yields and good chemoselectivity employing an air-stable and defined nickel catalyst, (bpy)Ni(OAc)(2). The oxidative cyclizations proceeded either through a six-membered or an unconventional seven-membered nickelacycle. An extensive mechanistic investigation by experiments and theoretical calculations revealed a facile indole's C(2)-H nickelation and a rate-limiting reductive elimination process. This intramolecular oxidative cyclization operates via a probable Ni(II)/Ni(III) pathway involving single-electron oxidation of nickel without the participation of a carbon-based radical.
Keywords: C-H activation; cycloindolones; indenoindolones; indoles; Mechanism; Nickel; oxidative coupling

Unactivated alkyl halides in transition-metal-catalyzed C-H bond alkylation - Ankade, Shidheshwar B.; Shabade, Anand B.; Soni, Vineeta; Punji, Benudhar (ACS Catalysis, 2021)
Alkylation represents an important organic transformation in molecular science to develop privileged alkylated arenes and heteroarenes. Especially, the direct C-H bond alkylation using unactivated alkyl halides is a straightforward and attractive approach from both the step-economy and chemoselectivity perspectives. Substantial progress has been made in the direct alkylation using primary, secondary, and tertiary alkyl halides along with the methylation and fluoroalkylation. This Review broadly summarizes the transition-metal-catalyzed alkylations of C-H bonds on various arenes and heteroarenes with unactivated alkyl halides until October 2020. On the basis of the substrates utilized for alkylation, the Review is divided into two major sections: alkylation of arenes and alkylation of heteroarenes.
Keywords: (hetero)arenes; Alkylation; C-H activation; transition metals; unactivated alkyl halides

Iridium-catalyzed synthesis of pyrazolone fused 1,4-dihydrocinnolin-3-one employing alpha-diazotized Meldrum's acid - Kulkarni, Anand M.; Mullapudi, Venkannababu; Ramana, Chepuri Venkata (ARKIVOC, 2022)
The [Iri-catalysed carbenoid insertion and cyclization of N-arylpyrazolones has been carried out with alpha-diazotized Meldrum's acid to access tricyclic pyrazolone fused 1,4-dihydrocinnolin-3-one derivatives. Further, the selective reduction of these tricyclic derivatives has been studied under Birch reduction conditions.
Keywords: ?-diazotized Meldrum's acid; C-H activation; carbene Insertion; cinnoline derivatives; N-arylpyrazolones; [Iri-Catalysis

Manganese-catalyzed C(sp(2))-H alkylation of indolines and arenes with unactivated alkyl bromides - Verma, Suryadev K.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Selective C(sp(2))-H bond alkylation of indoline, carbazole and (2-pyridinyl)arenes with unactivated alkyl bromides is achieved using MnBr2 catalyst in the absence of an external ligand. The alkylation uses a simple LiHMDS base and avoids the necessity of Grignard reagent, unlike other Mn-catalyzed C-H functionalization. This reaction proceeded either through a five- or a less-favored six-membered metallacycle, and tolerated diverse functionalities, including alkenyl, alkynyl, silyl, aryl ether, pyrrolyl, indolyl, carbazolyl and alkyl bearing fatty alcohol and polycyclic-steroid moieties. Alkylation follows a single electron transfer (SET) pathway involving 1e oxidative addition of alkyl bromide and a rate-limiting C-H metalation.
Keywords: Alkylation; C-H activation; indoline; ligand-free; manganese

Regioselectivity in metalloradical catalyzed C-H bond activation: a theoretical study - Mukherjee, Anirban; Singh, Ritesh; Mane, Kishor D.; Das, Gourab Kanti (Journal of Organometallic Chemistry, 2022)
Pure quantum mechanical calculations were performed to find out the origin of regioselectivity under the metalloradical catalysis (MRC) by Co(II)-porphyrin, which showed regioselectivity is the inherent property of the aminyl radical generated from the sulfamoyl azide substrate. Different conformational analysis for the transition state from alpha-Co-III-aminyl radical to zeta-Co-III-alkyl radical formation have been studied to find out the most stable conformation for the preferable selectivity. The outcome of our study completely agrees with the reported experimental results. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: C-H activation; DFT; Metalloporphyrin; Metalloradical; Regioselectivity

Rh-catalyzed C-H functionalization of the (Pyrazol-5-yl)pyridine core of GBT-440 - Kalshetti, Rupali G.; Halnor, Swapnil V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2023)
The Rh-catalyzed cross dehydrogenative coupling (CDC)/alkylation of the pyrazolylpyridine unit of GBT-440 proceeded smoothly under ambient conditions and selectively on the pyrazole unit while directed by the pyridine. The scope of these reactions was established by employing simple as well as conjugated olefins for CDC and various diazo esters and the TIPS-EBX reagent for alkylation. At the outset, a focused small molecule library around the bis-heterocyclic core of GBT440 was developed via C-H functionalization.
Keywords: C-H activation; cross dehydrogenative coupling; diazo ester; GBT-440; Rh catalysis; TIPS-EBX

Palladium-catalyzed regioselective C(4)-H fluoroalkoxylation of indoles through weak chelation assistance - Vijaykumar, Muniyappa; Gonnade, Rajesh G.; Punji, Benudhar (ChemCatChem, 2025)
Installing fluoroalkyl motifs into biorelevant indoles is particularly interesting due to their ubiquitous presence in drug molecules. Herein, we demonstrate the regioselective C4 fluoroalkoxylation of indoles using fluoroalcohols via palladium-catalyzed chelation-assisted C & horbar;H activation. The weak chelating benzoyl moiety at the C3 position acts as a directing group for remote C(4)& horbar;H fluoroalkoxylation of diversely substituted indoles. This methodology demonstrates a high level of regioselectivity and tolerates a range of crucial functional groups, yielding diverse trifluoroalkoxylated indoles in moderate to good yields. Removal of directing/protecting groups and further functionalization established the synthetic utility of the methodology. A preliminary mechanistic investigation is conducted by isolating the palladacycle intermediate and performing the deuterium scrambling study. The regioselective C4 fluoroalkoxylation of indoles with various fluoroalcohols is achieved by the palladium-catalyzed weak chelation assistance strategy. The reaction is compatible for a range of important functionalities and proceeds via the intermediacy of a six-membered palladacycle following a Pd(II)/Pd(IV) pathway. image
Keywords: C-H activation; indoles; Palladium; Regioselective; Trifluoroalkoxylation

Rational design of hydrophobic Cu/CuO electrodes for electrochemical oxygenation of tetralin: a strategic approach - Cherukuthota, Sri Vidya; Mathew, Elizabeth; Verma, Tushar Singh; Joshi, Krati; Selvaraj, Kaliaperumal (ChemSusChem, 2025)
Electro-organic synthesis presents a sustainable and practical alternative to traditional organic synthesis methods, which typically utilize harsh reagents and require energy-intensive conditions. Nevertheless, the challenge of achieving satisfactory conversion and selectivity rates in electrocatalytic oxidation using a non-platinum group metal (PGM) catalyst pair still needs to be addressed. This study demonstrates the application of a non-PGM-based catalyst pair for the electrocatalytic oxidation of tetralin to 1-tetralone, a highly demanded raw material in the pharma industry. Copper electrodeposited on teflonated carbon paper combined with copper foam as the electrocatalyst pair has demonstrated impressive conversion and selectivity ratios to electro-synthesize 1-tetralone at room temperature and atmospheric pressure. The optimal choice of a non-PGM catalyst, ideal mass loading, and a unique electrode configuration resulted in an ultimate conversion of about 99% of tetralin and 1-tetralone selectivity -93.7%, yield -92.6%. The reaction pathway associated with the electrochemical phenomena is supported by first principles-based density functional theory calculations and X-ray photoelectron spectroscopy of the electrocatalyst. This process has exceptional performance that can be adapted for a wide range of substrates and is straightforward, ambient, reagent-free, scalable, and therefore beneficial for industrial use. Therefore, initiatives have been taken in this direction.
Keywords: C-H activation; Copper; electrochemical oxidation; non-PGM electrocatalysts; tetralin; Tetralone